Pengaruh Perbedaan Waktu Belajar terhadap Hasil Belajar Bahasa Inggris Mahasiswa Universitas Teknologi Mataram - Wulandari, Aini Husnida (ARZUSIN, 2022)
This study aims to determine (1) Is there any effect of differences in learning time on English Learning Outcomes of 2nd Semester UTM Management Study Programs (2) How big is the effect of differences in study time on English Learning Outcomes of 2nd Semester UTM Management Study Program students by comparing the scores their Final Semester Examination scores. This research method is descriptive quantitative because it will process data in the form of Final Semester Exam (UAS) scores for English Course Students in the 2nd semester of the UTM Management Study Program. Data in the form of student scores were divided into 2 groups. Namely the value of students who study in the morning and the value of students who study in the afternoon. The 2 groups of data will be compared by looking at the highest value, lowest value and average value. The results of the analysis show that there is an effect of differences in study time on English Learning Outcomes of 2nd semester students of the UTM Management Study Program with the following comparison the maximum score of students in the morning is 95.00. The minimum score is 56.00 with an average of 82.33. While the value for afternoon students, the maximum score is 90.00, the minimum score is 56.00 with an average value of 76.80. The average score for students who study in the morning is higher than the average value of students who study in the afternoon.